Micromagnetism and the microstructure of ferromagnetic solids - Kronmuller, Helmut (Cambridge University Press, 2003)
Here is a fundamental introduction to microstructure magnetic property relations where microstructures on atomic, nano- and micrometer scales are considered. The authors demonstrate that outstanding magnetic properties require an optimization of microstructural properties where the microstructures in crystalline materials are point defects and dislocations as well as grain and phase boundaries. In amorphous alloys the type of microstructures on atomic scales are defined and used to describe intrinsic and extrinsic properties.